Race, sex, and Clarence Thomas: representation change in the EEOC - Meier, Kenneth; Eller, Warren S.; Pennington, Michael S. (2005)
The theory of representative bureaucracy concerns whether bureaucracy mirrors the origins and values of the population and, if so, whether such representation makes any difference. This article extends Hindera's examination of active bureaucratic representation within the Equal Employment Opportunity Commission (EEOC) to determine the effect of introducing new goals (disability discrimination) and priorities (sexual harassment) on the EEOC's representational patterns. Using data from the late 1980s and the late 1990s, we find the extent of active representation of African Americans declined. Although the EEOC is now pursuing more cases of sex discrimination, no evidence of active representation exists for women in EEOC district offices. - Reproduced.
Keywords: Equal Employment Opportunity Commission; Ethnic groups; Bureaucracy